2019
DOI: 10.1097/md.0000000000015022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ISUP grading of clear cell renal cell carcinoma using support vector machine model based on CT images

Abstract: Background: To explore whether radiomics combined with computed tomography (CT) images can be used to establish a model for differentiating high grade (International Society of Urological Pathology [ISUP] grade III–IV) from low-grade (ISUP I–II) clear cell renal cell carcinoma (ccRCC). Methods: For this retrospective study, 3-phase contrast-enhanced CT images were collected from 227 patients with pathologically confirmed ISUP-grade ccRCC (155 cases in the low-grade grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Burak Kocak et al provided a radiomic model to predict histopathologic nuclear grade by using the radiomic features extracted from unenhanced CT texture analysis of KIRC tumors (13). Other researches constructed classification models that preoperatively identified pathological grades of KIRC patients by using machinelearning-based CT radiomic with non-invasion (38)(39)(40)(41)(42)(43). Certain studies also showed the significance of CT radiomic in distinguishing KIRC from other renal mass diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Burak Kocak et al provided a radiomic model to predict histopathologic nuclear grade by using the radiomic features extracted from unenhanced CT texture analysis of KIRC tumors (13). Other researches constructed classification models that preoperatively identified pathological grades of KIRC patients by using machinelearning-based CT radiomic with non-invasion (38)(39)(40)(41)(42)(43). Certain studies also showed the significance of CT radiomic in distinguishing KIRC from other renal mass diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the WHO/ISUP grading system has been accepted in current medical practice, replacing the former Fuhrman grading system. To the best of our knowledge, there are only a few published papers that have studied radiomics features based on MDCT for predicting the ccRCC WHO/ISUP nuclear grade [ 29 , 48 , 49 , 50 , 51 ]. However, no previous work used parameters extracted from a four-phase MDCT study to develop the prediction model, as our study does.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, they showed that the combined model of radiomics features from two certain phases had the highest differential diagnostic efficiency (AUC: 0.82 (95% CI: 0.76–0.86). A recent study [ 51 ] showed that the value of the NP phase is limited in predicting the ISUP grade. This may be due to two reasons: firstly, regarding tumor delineation, Sun et al used a single-slice approach (largest cross-section diameter of the tumor) and did not perform data analysis of the entire tumor VOI.…”
Section: Discussionmentioning
confidence: 99%
“…The top-ranked models were reported by He et al with a predictive mean value of 92.5% ± 1.83% using ANN-based radiomics. The best accuracy (94.1% ± 1.14%) was achieved by combining texture features from conventional image which were calculated from manually selected regions of interest (ROI), such as mean attenuation, parenchyma attenuation and absolute enhance attenuation, and CMP [45,[48][49][50][51].…”
Section: Nuclear Grade Predictionmentioning
confidence: 99%